Egr-1 induction provides a genetic response to food aversion in zebrafish - Boyer, Brigitte; Ernest, Sylvain; Rosa, Frédéric (Frontiers in Behavioral Neuroscience, 2013)
As soon as zebrafish larvae start eating, they exhibit a marked aversion for bitter and acidic substances, as revealed by a consumption assay, in which fluorescent Tetrahymena serve as a feeding basis, to which various stimuli can be added. Bitter and acidic substances elicited an increase in mRNA accumulation of the immediate-early response gene egr-1, as revealed by in situ hybridization. Conversely, chemostimulants that did not induce aversion did not induce egr-1 response. Maximum labelling was observed in cells located in the oropharyngeal cavity and on the gill rakers. Gustatory areas of the brain were also labelled. Interestingly, when bitter tastants were repeatedly associated with food reward, zebrafish juveniles learned to ingest food in the presence of the bitter compound. After habituation, the acquisition of acceptance for bitterness was accompanied by a loss of egr-1 labelling. Altogether, our data indicate that egr-1 participates specifically in food aversion. The existence of reward-coupled changes in taste sensitivity in humans suggests that our results are relevant to situations in humans.